Evaluation of the effects of differences in silicone hardness on rat model of lumbar spinal stenosis - Kim, Hyunseong; Hong, Jin Young; Jeon, Wan-Jin; Lee, Junseon; Ha, In-Hyuk (PLOS ONE, 2021)
Lumbar spinal stenosis (LSS), one of the most commonly reported spinal disorders, can cause loss of sensation and dyskinesia. In currently used animal models of LSS, the spinal cord is covered entirely with a silicone sheet, or block-shaped silicone is inserted directly into the spinal canal after laminectomy. However, the effects of differences between these implant materials have not been studied. We assessed the degree of damage and locomotor function of an LSS model in Sprague-Dawley rats using silicone blocks of varying hardness (70, 80, and 90 kPa) implanted at the L4 level. In sham rats, the spinal cord remained intact; in LSS rats, the spinal cord was increasingly compressed by the mechanical pressure of the silicone blocks as hardness increased. Inflammatory cells were not evident in sham rats, but numerous inflammatory cells were observed around the implanted silicone block in LSS rats. CD68+ cell quantification revealed increases in the inflammatory response in a hardness-dependent manner in LSS rats. Compared with those in sham rats, proinflammatory cytokine levels were significantly elevated in a hardness-dependent manner, and locomotor function was significantly decreased, in LSS rats. Overall, this study showed that hardness could be used as an index to control the severity of nerve injury induced by silicone implants.